A Dynamic Brain Drain in Peripheral Regions - Miki Malul (European Regional Science Association (ERSA), 2012)
The aim of this research is to explore the effect of a lower return on education in peripheral regions of a country compared to core regions on the decision of individuals in each region to acquire human capital by advancing their education. In addition, the study examines how these decisions may endogenously increase the income gap between the core region and the peripheral region. We first build a theoretical model that explains the individual's decisions regarding the acquisition of human capital using different production functions in each region. Thereafter, we conduct a simulation, using data from Israel's Central Bureau of Statistics, to evaluate the main parameters of the model.
Keywords: 330